“Beyond Aid” and the future of development cooperation - Heiner Janus; Stephan Klingebiel; Sebastian Paulo (Deutsches Institut für Entwicklungspolitik (DIE), 2014)
Development cooperation is under pressure to change. The traditional aid model – a resource transfer from North to South – is outdated. There are only 36 low-income countries left in the world. Two-thirds of the poorest people live in middle-income countries. Eradicating poverty has become more complex. Aid is no longer used to only address income poverty but also a large variety of development challenges, including climate change, inequality and insecurity. Many of these challenges need to be addressed outside the traditional development cooperation sphere. Currently, it is not clear what will replace traditional aid. Observers often speak about a beyond aid future. As an umbrella term, beyond aid describes different aspects of the transformation of development cooperation. The transformation is particularly pronounced in four dimensions where aid is decreasing in relative importance: the proliferation of actors, the diversification of finance, the shaping of rules and policies, and the sharing of knowledge for development. The future of development cooperation depends on how the policy field learns to create linkages with these dimensions. This includes rethinking the relationship between the goals and instruments of development cooperation. Such a process is already ongoing and can lead in two main directions that are not mutually exclusive: development cooperation can specialise on poor countries and/or be integrated into the broader framework of global cooperation. In the case of specialisation, development cooperation retains the focus on poverty reduction and concentrates on an ever smaller number of mostly fragile countries. In the case of integration, development cooperation supports a more complex system of global development objectives, including the provision of global public goods. In both scenarios, development cooperation needs to strengthen its linkages with other areas of international cooperation along the four dimensions of beyond aid: actors, finance, regulation and knowledge. Although these partly overlapping scenarios are likely to play out simultaneously in the policy field as a whole, individual development actors face choices for their strategic orientation. For example, development actors need to consciously revisit their specific objectives for engaging in development cooperation. Is poverty reduction, the provision of global public goods or a mix of both the priority of their development cooperation? Depending on the answer, the allocation pattern of their budgets would differ. A global public goods allocation model would mark a departure from the predominant country allocation system, for instance. Also, development actors need to re-evaluate whether current principles for effective development cooperation are suitable for cooperation beyond aid. Thus, thinking through the scenarios of specialisation and integration of development cooperation in a beyond aid future should already be shaping the strategic decisions of development actors today.
Keywords: 330; Deutsche + Europäische + multilaterale Entwicklungspolitik; Regionale + globale + transnationale Governance